Piloting a Savings-Led Microfinance Intervention with Women Engaging in Sex Work in Mongolia: Further Innovation for HIV Risk Reduction - Tsai, Laura Cordisco (2011)
This paper describes a pilot study testing the feasibility of an innovative savings-led microfinance intervention in increasing the economic empowerment and reducing the sexual risk behavior of women engaging in sex work in Mongolia. Women’s economic vulnerability may increase their risk for HIV by compromising their ability to negotiate safer sex with partners and heightening the likelihood they will exchange sex for survival. Microfinance has been considered a potentially powerful structural HIV prevention strategy with women conducting sex work, as diversification of income sources may increase women’s capacity to negotiate safer transactional sex. With 50% of all reported female HIV cases in Mongolia detected among women engaging in sex work, direct prevention intervention with women conducting sex work represents an opportunity to prevent a potentially rapid increase in HIV infection in urban Mongolia. The piloted intervention consisted of a matched savings program in which matched savings could be used for business development or vocational education, combined with financial literacy and business development training for women engaging in sex work. Results of the pilot demonstrate participants’ increased confidence in their ability to manage finances, greater hope for pursuing vocational goals, moderate knowledge gains regarding financial literacy, and an initial transition from sex work to alternative income generation for five out of nine participants. The pilot findings highlight the potential for such an intervention and the need for a clinical trial testing the efficacy of savings-led microfinance programs in reducing HIV risk for women engaging in sex work in Mongolia.